PEDAGOGICAL POSSIBILITIES OF THE WORK “THE WHITE SHIP” IN DEVELOPING EMPATHY IN STUDENTS - Shoyimova Shoira Sanakulovna (International Journal of Literature and Language Studies, 2026)
The article analyzes the pedagogical potential of fiction, in particular Chingiz Aitmatov's story